2012
DOI: 10.7314/apjcp.2012.13.8.3573
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Diagnostic Aids in Oral Cancer

Abstract: Oral cancers are one of the most common cancers worldwide today. They are usually neglected by the common population when compared to systemic cancers such as the lung cancer, colon cancer etc. However, they also may be extremely fatal if left untreated even at a very initial stage of the lesion. Early detection and treatment gives the best chance for its cure. The five-year survival rate of oral cancer still remains low and delayed diagnosis is suggested to be one of the major reasons. The detection and diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…Several diagnostic techniques have been proposed to help in screening and early detection of oral cancer (Scully et al, 2008;Masthan et al, 2012). Scalpel biopsy, however, is considered the gold standard in oral cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several diagnostic techniques have been proposed to help in screening and early detection of oral cancer (Scully et al, 2008;Masthan et al, 2012). Scalpel biopsy, however, is considered the gold standard in oral cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Also, several studies have shown a relation between the users of smokeless tobacco and oral cancer (5-9). …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies show that usage of tobacco may be the leading cause of oral cavity and oropharyngeal cancer development and it is believed that smokers are more likely to develop oral cancer than nonsmokers. Carcinogens, which are present in high concentration in tobacco and its products and are also the leading cause of cancer in lungs, esophagus and several other organs (Masthan et al, 2012). More than 400,000 cases of oral and pharyngeal cancers diagnosed annually, with almost two-thirds of them found among male (Ferlay et al, 2010).…”
Section: Introductionmentioning
confidence: 99%